2001
DOI: 10.1038/sj.ejcn.1601115
|View full text |Cite
|
Sign up to set email alerts
|

Catechin intake and associated dietary and lifestyle factors in a representative sample of Dutch men and women

Abstract: Objective: To study the intake of catechins in the Dutch population and to assess the relation between catechin intake and other dietary factors. Catechins, dietary components that belong to the¯avonoid family, potentially protect against chronic diseases such as cancer and cardiovascular diseases. Catechins are the major components of tea, but they are present in many other plant foods as well. Design: Data were used from a nationwide dietary survey carried out in 1998 among a representative sample of 6200 Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 18 publications
2
80
2
3
Order By: Relevance
“…A daily consumption of 50 g olive oil with a concentration of 180 mg/kg of phenols would result in an estimated intake of about 9 mg of olive oil phenols per day. This is similar to the intake of flavonols and catechins from apples (about 10 mg/day), but lower than that of catechins from tea (50 mg/day) (Arts et al, 2001) or phenolic acids from coffee (200 mg/day) (Radtke et al, 1998). However, it is difficult to compare those intakes in terms of antioxidant activity because the antioxidant potential as well as the bioavailability might differ among various antioxidants.…”
Section: Chemistry and Content Of Phenols In Olive Oilsupporting
confidence: 56%
See 1 more Smart Citation
“…A daily consumption of 50 g olive oil with a concentration of 180 mg/kg of phenols would result in an estimated intake of about 9 mg of olive oil phenols per day. This is similar to the intake of flavonols and catechins from apples (about 10 mg/day), but lower than that of catechins from tea (50 mg/day) (Arts et al, 2001) or phenolic acids from coffee (200 mg/day) (Radtke et al, 1998). However, it is difficult to compare those intakes in terms of antioxidant activity because the antioxidant potential as well as the bioavailability might differ among various antioxidants.…”
Section: Chemistry and Content Of Phenols In Olive Oilsupporting
confidence: 56%
“…Therefore, it is difficult to compare the antioxidant effect of olive oil phenols in vivo with that of phenols from other foods, like wine, coffee, tea, onions, or apples. Nevertheless, intake of phenolic compounds from tea is some 50 mg/day (Arts et al, 2001) or that from coffee 200 mg/day (Radtke et al, 1998). This is much higher than the intake of 2 mg/day of hydroxytyrosol equivalents from olive oil in the Mediterranean diet.…”
Section: Are Phenols Antioxidants In Vivo?mentioning
confidence: 99%
“…Grapes contain a wide variety of polyphenol compounds, including flavonoids, phenolic acids, and resveratrol. There is extensive epidemiological evidence suggesting that dietary intake of these compounds reduces cardiovascular mortality (12)(13)(14)(15)(16)(17). Numerous studies in vitro as well as in animals and humans demonstrate beneficial effects of grape polyphenols on traditional cardiovascular risk factors ( Table 1).…”
Section: Epidemiologymentioning
confidence: 99%
“…Numerous studies in vitro as well as in animals and humans demonstrate beneficial effects of grape polyphenols on traditional cardiovascular risk factors ( Table 1). Population-based studies have observed markedly lower cardiovascular disease mortality in cohorts with higher consumption of relevant flavonoids, including flavonols, flavones, and flavan-3-ols (13)(14)(15)(18)(19)(20). In a study of 34,489 postmenopausal American women, dietary intake of foods containing flavanones and anthocyanidins was associated with decreased cardiovascular and all-cause mortality (21).…”
Section: Epidemiologymentioning
confidence: 99%
“…6 Apples have significant amounts of polyphenolic compounds 7 and are an important source of flavonoids in peoples' diets in the United States of America and Europe. 8 Effective absorption of the apple polyphenols from the mammalian colon has been shown in vivo and in vitro. 9,10 Other than antioxidative effects 11 and their ability to scavenge carcinogens, the apple polyphenols may be chemoprotective by affecting molecular events in the initiation, promotion and progression stages of carcinogenesis.…”
mentioning
confidence: 99%